MYH9 promotes malignant progression of glioma cells through regulating β-catenin stability via epithelial-mesenchymal transition signaling pathway - Zigui Chen; Chao Liu; Wei Zheng; Zhilong Li; Yuanhui Tang; Jun Peng; Changfeng Miao; Dandan Zheng; Ying Xia (Scientific Reports)
Abstract Epithelial‒mesenchymal transition (EMT) is a process in which polar epithelial cells transform into active mesenchymal cells and acquire invasion and migration capabilities (Cano CE, Motoo Y, Iovanna JL in Sci World J 10, 2010). EMT is involved in multiple physiological and pathological processes in the human body. The occurrence of EMT involves many signal transduction pathways and complex molecular mechanisms related to calnexin, growth factors, transcription factors, and the microenvironment. EMT is closely related to the invasion and metastasis of tumour cells. The MYH9 gene is closely associated with tumour progression. However, the function and regulatory mechanism of MYH9 in tumour occurrence and development remain unclear. Herein, we revealed for the first time that the migration, invasion, and metastatic abilities of glioma cells decreased significantly after MYH9 expression was downregulated. Moreover, our results suggested that MYH9 regulated the epithelial‒mesenchymal transition (EMT) process in glioma cells via β-catenin. In this mechanism, MYH9 was shown to bind to β-catenin and to increase its protein level by recruiting the deubiquitinase USP2 to form a complex. This complex suppressed β-catenin protein degradation, ultimately enhancing EMT signal transduction. This MYH9/β-catenin/EMT pathway represents a new molecular mechanism involved in the invasion promotion in gliomas. Our findings also demonstrated that MYH9 was crucial for inducing glioma cell migration. In summary, we suggest that MYH9 is a potential molecular marker for predicting tumour progression and prognosis and highlight its role in a new molecular mechanism of tumour metastasis.